Solo: Io e Ischia. L’Isola Verde attraverso Pier Paolo Pasolini - Petrone, Federica (Kritik. Rivista di letteratura e critica culturale, 2024)
The paper aims to reconstruct the relationship between Pier Paolo Pasolini and the island of Ischia. The aim is, firstly, to illustrate the stages of this encounter and its modalities: the writer, in fact, first got to know the island through the eyes of the painter Luigi De Angelis and then went there in person, with the aim of producing a reportage on the Italian beaches. On the other hand, the intention is to highlight the value that the island assumed in Pasolini’s eyes, the meanings with which it and its inhabitants are charged within its pages.